Pengaruh Keadilan Distributif, Keadilan Prosedural, dan Gaya Kepemimpinan terhadap Fraud - Luh Putu Devia Aditya; Lucy Sri Musmini (Universitas Pendidikan Ganesha, 2021)
Fraud is an act of fraud committed to obtain personal gain by harming other parties. Fraud often occurs in both government and private institutions. This study aims to determine how the influence of distributive justice, procedural justice, and leadership style on fraud. In this study, the researcher used the research method of distributing questionnaires with saturated sampling technique. The study was conducted on all civil servants and non-civil servants at the BKPSDM Office of Buleleng Regency with a total sample of 100 respondents. The results of this study indicate that distributive justice, procedural justice, and leadership style have a negative effect on fraud. This means that the better the conditions of procedural justice, distributive justice, and the applied leadership style will suppress the occurrence of fraud in the company or organization